Influence of quality performance on clients’ patronage of indigenous and expatriate construction contractors in Nigeria - Idoro, Godwin Iroroakpo (Journal of Civil Engineering and Management, 2010)
Contractors operating in Nigeria are classified as either indigenous or expatriates. The latter is often giving preference over the former in the award of contracts and stakeholders consider this practice unhealthy for growth and development. This study evaluates the influence of the quality performance of the two categories of contractors on their patronage. The objectives are to determine the level and difference in the patronage and quality performance of indigenous and expatriate contractors and the correlation between clients’ assessment of the quality performance and patronage of indigenous and expatriate contractors in the Nigerian construction industry. To achieve these objectives, a field survey involving a sample of 43 clients selected from the population of organised clients in Nigeria was conducted. Structured questionnaires were used to collect data. The data collected were analysed to determine the ranking and test of difference in clients’ patronage and clients’ assessment of quality performance between the two categories of contractors using mean and t‐test respectively. The correlation between patronage and quality performance was analysed using Spearman correlation test. The study established that expatriate contractors are being giving preference in the award of contracts. It also established that clients perceive the quality performance of expatriate contractors to be better than that of indigenous contractors and attributed the preference in patronage to this difference. It suggested that indigenous contractors should embark on measures that will improve their quality performance in order to stop the preference for expatriate contractors. Published Published Online: 14 Oct 2010